The Role of Unit IV PPA Regional Police of Province, Sulawesi Selatan and Teachers Association of Indonesia Branch Province, South Sulawesi in Implementing the Supreme Court Decision on Teachers That Cannot Be Convicted In The Implementation Of Its Duty - Kadriah, Awaluddin; Mas, Marwan; A. Hasan, yulia (Indonesian Journal of Legality of Law, 2018)
This study aimed at determining the role of the Police and Indonesian Teachers Association (Persatuan Guru Republik Indonesia) of South Sulawesi in implementing Restorative Justice against teachers who are dealing with the law due to the implementation of sanctions in educating, whether it is in accordance with the Supreme Court jurisprudence about teachers who cannot be convicted in carrying out their duties to educate, and how to implement restorative justice for teachers in the pre-adjudication stage in criminal justice system. The research method used was descriptive analysis with data from field interviews and literature. The study concluded that the role of the Police and PGRI in South Sulawesi in implementing Restorative Justice was not yet optimal, as evidenced by the fact that some cases of teachers were not resolved by Restorative Justice at the police stage in some areas in South Sulawesi. The instrument used was still in the form of discretion so that its use can differ from one investigator to another. PGRI in South Sulawesi in carrying out the facilitative function for teachers who are facing legal proceedings has not been coordinated in several districts and a memorandum of understanding has not yet been established at the provincial and district level between the Police and PGRI in South Sulawesi in handling teachers who face legal processes due to carrying out educational tasks. The agreement built must consider the Supreme Court's ruling on teachers who cannot be convicted in carrying out their duties to educate.